DESAIN SISTEM PAKAR UNTUK INTERPRETASI BAGAN KENDALI MUTU PAKAN - Erlin Trisyulianti, Yandra Arkeman, Hatrisari Hardjomidjojo dan Asep Saefuddin (Department of Agroindustrial Technology, Bogor Agricultural University, 2005)
ABSTRACTThe objective of feed production process is to generate high quality of feed livestock with parameter good physical, nutrition characteristics, continuity, palatability and safety feed. It is needs to be supported by optimum performance of process production. Control chart are the most effective tool to analyze performance of production process. The general objective of this research is to study quality control system and application of quality management in feed production industry. The spesific objective in this research is to design an expert system for feed control chart interpretation based on basic knowledge being made by doing knowledge acquisition.Feed control chart interpretation was conducted to analyze factors that caused uncontrollable condition in feed production. Interpretation control chart that is usually carried by expert, for this practical function in feed industry, furthermore designed in expert system.Model design was conducted in two steps, (1) preparation, and (2) development, System development consisted of (a) basic knowledge development in knowledge acquisition, knowledge conceptualization, and knowledge representation, (b) development of inference mechanism, (c) coding, and (d) verification.The Expert System showed that if data distribution is random and normal, then process is in controllable condition. If it shows one of seven patterns (one point out of control, cycles, mixture pattern, trend, a shift in process level, six point in a row under or upper median and stratification), then the process is confirming uncontrollable condition. If process is uncontrollable, expert system would interpreet the causes and recommend that it should be done by supervisor/operator.Keywords: expert system, intrepretat, control chart, process, feed